On the equiconvergence of the spectral decomposition of the distributions connected with elliptic differential operators on the torus with Fourier integral - Akhmedov, Abdulkasim; Zuki, Salleh; Rakhimov, Abdumalik (IOP Publishing, 2021)
In this paper, we deal with the problems of the expansions of the periodic distributions. We obtained sufficient conditions for the equiconvergence of the spectral decompositions of the distributions connected with the elliptic differential operator on the torus with Fourier integral in the classes of the Sobolev.